PENGARUH KOMPETENSI DAN PENGAWASAN TERHADAP KINERJA PEGAWAI PADA SATUAN POLISI PAMONG PRAJA DAN PEMADAM KEBAKARAN KABUPATEN MUSI RAWAS - Nasruddin, Nasruddin (Ensiklopedia of Journal, 2018)
This study examines the effect of competence and supervision on the performance of employees in the Civil Service Police and Fire Department Musi Rawas Regency. This research method uses questionnaire method, namely competency questionnaire, supervision questionnaire and employee performance questionnaire using SPSS 20. Based on the results of the t test can be explained as follows: that the competency variable (X1) on the performance of employees in the Musi Rawas District Civil Service Police and Fire Department shows a value of t = 2.077 greater than the value of t table, 2,000 with a significant level = 0,000